An unusual case of Takayasu′s arteritis: Evaluation by CT angiography - Mukund Vidhate; Ravindra Kumar Garg; Rajesh Yadav; Neera Kohli; Praveen Naphade; H K Anuradha (Annals of Indian Academy of Neurology, 2011)
Takayasu′s arteritis is a chronic, idiopathic, medium and large vessel vasculitis involving aorta and its main branches. Frequent neurological manifestations include postural syncope, seizures, and blindness. Stroke, as presenting feature of Takayasu′s arteritis, is unusual. CT angiography reveals characteristic involvement of aortic arch and its branches. Involvement of intracranial vasculature is rather unusual. We are describing an unusual patient of Takayasu′s arteritis who presented with recurrent disabling syncopal attacks and had extensive involvement of intracranial vasculature. CT angiography revealed severe involvement of aortic arch. There was near complete occlusion at origins of both subclavian arteries, distal flow was maintained by collateral vessels along the chest wall. There was near total occlusion (at origin) of right common carotid with normal flow in distal part. The left common carotid was more severely involved showing greater than 80% narrowing in proximal half of the vessel. CT angiography also revealed involvement of left internal carotid artery, narrowing of left middle cerebral artery and involvement of cortical vessels. Patient was treated with oral corticosteroids. She improved remarkably after two and half months of follow up.